Disitamab Vedotin (RC48) combined with bevacizumab for treatment of HR-negative/HER2-positive metastatic breast cancer with liver and brain involvement: A case report - Qu, Fei; Liu, Qian; Lu, Rongrong; Li, Wei (Frontiers in Oncology, 2023)
Background: The overexpression of human epidermal growth factor receptor 2 (HER2) is strongly correlated with an elevated risk of developing distant metastases, particularly brain metastases, in breast cancer (BC) cases. RC48 (also known as Disitamab vedotin), represents a promising antibody-drug conjugate (ADC), that comprises three well-defined components: hertuzumab against the prominent tumor target-HER2, monomethyl auristatin E (MMAE) and a cleavable linker. Preclinical studies have demonstrated its robust antitumor activity in BC patient-derived xenograft models with HER2-positive or HER2-low expression. Additionally, antiangiogenic drugs like bevacizumab have shown potential efficacy on advanced BC via inhibiting pathological neovascularizationits. Case Presentation: Here, we will share our experience in treating a 49-year-old woman initially diagnosed with stage IV breast cancer characterized by hormone receptor (HR)-negativity and HER2-positivity. This complex case entailed brain and liver metastases, and the patient exhibited resistance to various HER2-targeted treatment regimens. Finally, the patient received RC48 plus bevacizumab as the advanced forth-line treatment, which was well tolerated with no observed toxicities. Subsequent radiological assessments revealed remarkable regression in the brain metastatic lesions, classified as having partial response based on the RECIST 1.1 system. The period of progression-free survival (PFS) was 7 months. Conclusion: The present study underscores the efficacy of systemic treatment with RC48 in conjunction, showcasing substantial enhancement in both radiographic indicators and clinical symptomatology among patients with brain metastatic breast cancer (BMBC). More specifically, the sequential application of ADCs in combination with antiangiogenics presents a novel avenue for advancing the treatment landscape of metastatic BC.